Analysis of Teacher Readiness and Difficulties in Implementing the Independent Learning Curriculum in Junior High Schools - Prihantini (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The teacher's task in the independent learning curriculum was to prepare a learning implementation plan, compile material, prepare assessments, ensure changes in student behavior, and carry out evaluations. However, 52% of students visited by researchers received grades below standard. The article was to determine the obstacles and difficulties teachers that have in implementing the Independent Learning Curriculum. The researchers used mixed methods approach. The respondents in this research were 66 teachers. Data collection techniques used surveys with instruments that have been developed. This instrument was assessed on a Likert scale of 1 to 5 points. Data collection used observation, interviews with 10 teachers, and documents related to research indicators. Analysis data technique used SPSS Version 25.0. Then data from observations, interviews and documentation were collected, reduced, coded, diversified and conclusions drawn. As a result, it was found that the learning implementation plan was incomplete, the teacher did not prepare the material himself, and the assessment method was not yet structured. It was also found that teachers lacked mastery of the material. From the survey it was found that 62.87% of teachers' learning implementation plans did not comply with implementation, 68.53% of teachers lacked mastery of the material, there were 72.10%, there were 56.92% changes in behavior and 54.20% did not evaluate learning.